Coverage area of path planning mobility model for screening post-disaster area / Intan Nabina Azmi ... [et al.] - Azmi, Intan Nabina; Mohd Yussoff, Yusnani; Kassim, Murizah; Md Tahir, Nooritawati (Universiti Teknologi MARA, 2021)
Recently, drone has been widely used for numerous application. One of them includes research on a drone for efficient services with minimal cost and risk. Due to the limitation of drone battery lifetime, an optimum flight pattern is needed to avoid power loss during flying while being able to effectively scan the required area. Hence, this paper presents an analysis of drone optimum flying pattern to achieve the highest coverage for limited time and energy consumption. The study focuses on site surveying application intended for post-disaster area. The analysis was conducted using OMNeT++ simulator version 5.2.1. The outcome from the analysis shows that the percentage of the coverage area for Zigzag and Square patterns increase by 13.03% and 17.67% at 20m height compared to 10m height using DJI Phantom 3 Standard. Initial results from the numerical analysis also show that the specification of the camera and the height of the flying drone has a huge impact to gain a wider coverage area. The findings from the study help to identify the optimum camera technical specification for the search and rescue mission considering that post-hazardous situation which has a great deal of limitations to human access.